ROLE OF FOOD PROCESSING INDUSTRY IN REGIONAL ECONOMIC DEVELOPMENT (Scientific journal of the Fergana State University, 2025)
The food processing industry plays a pivotal role in Uzbekistan's regional economic development by generating employment, enhancing value addition, and boosting export earnings. This study examines the sector's contributions, challenges, and potential for growth, emphasizing technological innovation, policy support, and market access. Findings reveal significant opportunities for economic transformation, alongside barriers such as limited technology adoption and infrastructure gaps. Strategic interventions are proposed to position Uzbekistan as a regional leader in sustainable food processing and economic development.